THE IMPLEMENTATION OF THE POLICY FOR THE DEVELOPMENT AND MANAGEMENT OF STREET VENDORS IN PARE-PARE CITY - Melati Melati; Haedar Akib; Andi Aslinda (Universitas Negeri Makassar, 2026)
This research includes show that the Implementation of the Policy for the Development and Management of Street Vendors in Parepare City. This can be seen from the results of interviews which show that the implementation of the Street Vendor Development and Management Policy has gone quite well, as well as street vendors' awareness of guidance and management showing good results. And seen from the policy implementation theory according to Merilee S. Grindle, it consists of indicators: Interests influenced by the policy, type of benefits produced, degree of change desired, location of decision making, program implementers, sources involved, power, interests, and strategies of the actors involved, Characteristics of institutions and authorities, Compliance and responsiveness. However, there are still indicators that are not good in the implementation of the PKL Development and Arrangement Policy, namely indicators of the power, interests and strategies of the actors involved, where the Satpol PP carries out socialization activities regarding the guidance and structuring of PKL on a regular basis but most of the PKL still do not follow or violate regional regulation No. 7 of 2019 concerning public order.